KVPO4F and KVOPO4 toward 4 volt-class potassium-ion batteries. Issue 37 (26th April 2017) - Chihara, Kuniko; Katogi, Akihiro; Kubota, Kei; Komaba, Shinichi
Abstract : Structurally identical KVPO4 F and KVOPO4 are evaluated as positive electrode materials for non-aqueous potassium-ion batteries. Abstract : Structurally identical KVPO4 F and KVOPO4 are evaluated as positive electrode materials for non-aqueous potassium-ion batteries. KVPO4 F and KVOPO4 show highly reversible potassium extraction/insertion with discharge capacities of ca. 92 mA h g −1 and ca. 84 mA h g −1, respectively, and their average discharge voltage reaches above 4.0 V with 1 M KPF6 EC/PC electrolyte at 2.0–5.0 V. Despite the extraction of large potassium-ions, their lattice volume shrinkages after charging to 5.0 V are 5.8% for KVPO4 F and 3.3% for KVOPO4, leading to stable cycle performance. This is the first report to confirm the charge/discharge behaviours of vanadium phosphate electrodes in 4 V-class K cells.